An Analysis of the Effects of Macroeconomic Fundamentals, Firm Growth, Capital Structure, and Firm Liquidity on Stock Returns, Dividend Policy, and Financial Performance Among Companies in the Non-Cyclical Consumer Sector Listed on the Indonesia Stock Exchange from 2021 to 2024 - Linda Afifah; Hwihanus Hwihanus (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the transmission mechanisms connecting macroeconomic fundamentals, firm growth, capital structure, and corporate liquidity to stock returns, utilizing dividend policy and financial performance as intervening variables. Focusing on public firms within the non-cyclical consumer sector listed on the Indonesia Stock Exchange from 2021 to 2024, data were collected using purposive sampling and evaluated via Structural Equation Modeling Partial Least Squares. The empirical findings reveal that external macroeconomic dynamics and internal firm growth exert influential pressure on baseline operational metrics and structural policies. However, capital structure and cash distribution frameworks remain largely insulated from immediate capital market adjustments, indicating that dividend variations do not serve as direct drivers of equity valuation. Conversely, short-term liquidity maintenance establishes an operational drag on internal profitability, whereas robust financial performance acts as the definitive mediating catalyst that optimizes investor yields. Ultimately, equity market returns are dictated by sustainable corporate profit generation rather than external financing structures, requiring executives to prioritize resource allocation efficiency over superficial payout modifications to successfully capture long-term public investor confidence.